METODE BALANCED SCORECARD (BSC) SEBAGAI ALAT PENGUKURAN KINERJA PERUSAHAAN PADA PT UNILEVER INDONESIA TBK - Novelia Ananda; Maria Yovita R.Pandin (Jurnal Mutiara Ilmu Akuntansi, 2023)
The Balanced Scorecard is part of the strategy-based success measurement concept. The balanced scorecard is a management tool used in measuring company performance with four perspectives, namely a financial perspective, a customer perspective, an internal business process perspective, and a growth and learning perspective. The article aims to see how PT Unilever Indonesia Tbk's performance is measured using the balanced scorecard method. This article is qualitative in nature and the data used is secondary data in the form of PT Unilever Indonesia's financial statements for the period 2018 - 2021. The results of this article can be concluded that the company's performance in the period 2018 - 2021 when compared to 2019 and 2020 got quite good results compared to with 2021 which got less good results. So it can be said that performance measurement can use the balanced scorecard as a tool to measure company performance as a whole.